Rethinking sexual and reproductive health and rights for young women in Southern Africa : a critical perspective - Crankshaw, Tamaryn; Freedman, Jane; Aantjes, Carolien; Poku, Nana, 1971- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
This important book provides a critical examination of the sexual and reproductive health and rights (SRHR) of young women and girls in Southern Africa, examining the ways in which current policies and programmes aimed at improving SRHR often fail to reach the most marginalised populations. Addressing key regional challenges such as high rates of HIV, unintended pregnancies, unsafe abortions, and sexual and gender-based violence, the book highlights how health inequalities in the region are in fact increasing, despite the 2030 Agenda for Sustainable Developmentof "leaving no one behind".The bookdraws on theoretical analysis and empirical data gathered from studies carried out in five Southern African countries (Madagascar, Mozambique, South Africa, Zambia, and Zimbabwe), arguing that a continued focus on HIV and interventions that target health in a narrow sense often fail to understand the wider socio-economic determinants of poor sexual andreproductive health and the ways in which girls and young women are made vulnerable. Written by leading scholars in the field, this will be essential reading for students and researchers in Global Health, International Development, Women's Studies, and all related fields.
Introduction -- Understanding and identifying vulnerability in SRHR research and policy -- Understanding the vulnerabilities of sexual-economic exchange -- Going beyond HIV: shifting the dialogue from risk to rights -- Sexual and gender-based violence: the most pressing challenge for SRHR? -- Conclusion: vulnerability and climate change.
Keywords: Reproductive rights -- Africa, Southern; Women's rights -- Africa, Southern; Women's health services -- Africa, Southern; MEDICAL / Public Health; SOCIAL SCIENCE / Women's Studies